Development of a Creativity Assessment Instrument for Prospective Biology Teachers in the Bioedutainment Course - Hadiyanti, Lutfia Nur; Marianti, Aditya; Sukaesih, Sri; Asmara Bening, Roswita; Sabiliriski Ishari, Achmad; Amanda Putri, Vonny (Universitas Negeri Semarang, 2025)
Biology Education students, as prospective biology teachers, must be equipped with the knowledge and skills to deliver biology lessons in an engaging and enjoyable manner. In the context of the JAS (Exploration of the Surrounding Environment) approach, Bioedutainment is a teaching strategy that aligns well with the JAS approach. Bioedutainment is a course within the curriculum of the Biology Education programme at FMIPA UNNES. The aim of this study is to develop a valid and reliable instrument to assess the creativity of students enrolled in the Bioedutainment course, specifically in designing and implementing engaging biology lessons based on the Bioedutainment strategy. This research utilises the ADDIE R&D model. The developed creativity instrument is described in terms of its characteristics, validated through expert judgment, and its reliability is measured using construct reliability coefficients (Cronbach's Alpha). The findings indicate that the three developed creativity assessment instruments align with the creativity aspects of fluency, flexibility, elaboration, and originality. Expert evaluations show that the instrument is suitable for use, and the reliability coefficient (CR) calculation yielded a score of 0.9, indicating that the developed creativity assessment instrument is reliable. In conclusion, the developed creativity assessment instrument, aligned with the established creativity assessment characteristics, is both valid and reliable for measuring the creativity of students in the Bioedutainment course